2004
DOI: 10.1080/03009740310004856
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against cyclic citrullinated peptide (CCP) and levels of cartilage oligomeric matrix protein (COMP) in very early arthritis: relation to diagnosis and disease activity

Abstract: This study confirms the high diagnostic specificity of anti-CCP antibodies for rheumatoid arthritis (RA) in a prospective population-based study of very early arthritis. Raised serum COMP levels were common in all diagnosis groups in this series, indicating cartilage involvement in both self-limiting and non-erosive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 5 publications
3
26
0
1
Order By: Relevance
“…With regard to RA specificity, anti-citC1 III -P antibodies did not differ from anti-CCP autoantibodies, which could also be detected in very few patients suffering from rheumatic conditions other than RA, in good agreement with earlier studies [21,22]. In addition, the frequency of positive testing for anticitC1 III -P antibodies (40.4%) in our RA inception cohort was only slightly reduced compared to anti-CCP IgG results (49.8%) that confirmed published studies in early RA [23]. Accordingly, a significant correlation was obtained between serum anti-CCP-IgG and anti-citC1 III -P-IgG titers in the RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to RA specificity, anti-citC1 III -P antibodies did not differ from anti-CCP autoantibodies, which could also be detected in very few patients suffering from rheumatic conditions other than RA, in good agreement with earlier studies [21,22]. In addition, the frequency of positive testing for anticitC1 III -P antibodies (40.4%) in our RA inception cohort was only slightly reduced compared to anti-CCP IgG results (49.8%) that confirmed published studies in early RA [23]. Accordingly, a significant correlation was obtained between serum anti-CCP-IgG and anti-citC1 III -P-IgG titers in the RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…A key posttranslational modification in autoimmunity appears to be the citrullination of arginine amino acid residues, by the enzymatic deimination of arginine to citrulline (Eggleton et al 2008;Doyle and Mamula 2012). This reaction is catalyzed by the enzyme peptidyl arginine deiminase (PAD) (Soderlin et al 2004). In multiple sclerosis and RA, citrullinated isoforms of myelin basic protein (Moscarello et al 2007) and fibrin (Masson-Bessiere et al 2001) have been found in the brain and synovia, respectively.…”
Section: Relationship With Other Autoimmune Diseases (Altered Antigens)mentioning
confidence: 99%
“…[17][18][19] Recent studies have described the occurrence of anti-CCP in 41-68% of patients with early RA. [20][21][22][23][24][25][26] However, up to 90% of anti-CCP positive patients were also positive for RF 20 21 24 and cooccurrence of both antibodies was not more specific for RA than occurrence of either antibody alone. 25 27 Given this frequent concurrence of RF and anti-CCP as well as the economic impact of broad anti-CCP testing, we investigated if autoantibody profiling by sequential testing at first presentation might have diagnostic and prognostic value in differentiating RA from other arthritic disorders in an inception cohort of patients with very early inflammatory joint disease.…”
mentioning
confidence: 99%